2021
DOI: 10.1109/jstars.2021.3062073
|View full text |Cite
|
Sign up to set email alerts
|

Application of Landsat ETM+ and OLI Data for Foliage Fuel Load Monitoring Using Radiative Transfer Model and Machine Learning Method

Abstract: Foliage fuel load (FFL) is a critical factor affecting crown fire intensity and rate of spread. Satellite observations provide the potential for monitoring FFL dynamics across large areas. Previous studies commonly used empirical methods to estimate FFL, which potentially lacks reproducibility. This study applied Landsat 7 ETM+ and 8 OLI data for FFL retrieval using radiative transfer model (RTM) and machine learning method. To this end, the GeoSail, SAIL and PROSPECT RTMs were firstly coupled together to mode… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 28 publications
(5 citation statements)
references
References 91 publications
(117 reference statements)
0
5
0
Order By: Relevance
“…where ρ BLUE is MODIS data band 01, ρ RED is MODIS data band 02, ρ NIR is MODIS data band 03, and ρ SWIR is MODIS data band 07. In the upper model, PROGeoSAIL, the FMC estimate formula is [33,34]…”
Section: Sensitivity Analysismentioning
confidence: 99%
“…where ρ BLUE is MODIS data band 01, ρ RED is MODIS data band 02, ρ NIR is MODIS data band 03, and ρ SWIR is MODIS data band 07. In the upper model, PROGeoSAIL, the FMC estimate formula is [33,34]…”
Section: Sensitivity Analysismentioning
confidence: 99%
“…Topography can play a key role in governing bushfire severity patterns over a landscape [5], [10]- [14]. Many studies have identified that climate and fuel variables significantly influence bushfire severity [10], [15]- [17] but the situation is complex in hilly landscapes. In a hilly region, topography can not only govern fire behaviour but also influence the local micro-climate and fuel distribution of the area [12], [18], [19].…”
Section: Introductionmentioning
confidence: 99%
“…Fuel is another critical element for fire ignition, spread, and combustion. The fuel variables, such as land cover or land use, live fuel moisture content (LFMC) (Quan et al 2015;Quan et al 2017) and dead fuel moisture content (DFMC) (Resco de Dios et al 2015), fuel load (FL) (Quan, Li et al 2021), forestry type (FT), and tree species (TS) play important roles in wildfire probability prediction, since they have an important influence on fire behaviors and regimes (Cao et al 2017;Jaafari et al 2017;Luo et al 2019;Carrasco et al 2021;Gale et al 2021;Quan, Xie et al 2021). Among them, the live and dead fuel moisture contents are most commonly considered in wildfire probability modeling at present (Yebra et al 2013;Nolan, Boer et al 2020;Quan, Xie et al 2021) because the large-scale and dynamic monitoring of these variables is available, either from remote sensing data or meteorological data (Yebra et al 2008;Nolan et al 2016;Fan and He 2021;Quan, Yebra et al 2021).…”
Section: Introductionmentioning
confidence: 99%